Conocimientos, mitos y creencias sobre la salpingectomía y su relación con la decisión para acceder al procedimiento en pacientes del Hospital Martín Icaza, septiembre 2024 – marzo 2025. - Castro Párraga, Karla Stefania (2024)
Salpingectomy is an effective procedure to diminish any effect of female non-planning, thus reducing maternal and infant morbidity and mortality. At present, the difficulty lies in the scarcity of information and the distortion of salpingectomy, it is crucial to assess the level of knowledge that patients have about salpingectomy. Therefore, this study was focused on analyzing the influence of the level of knowledge, myths and beliefs about salpingectomy, which affect the decision to undergo the procedure in patients of the Hospital General Martín Icaza of Babahoyo. Using a non-experimental methodology, complemented with a field study, descriptive, cross-sectional, using the deductive method, framed in the quantitative methodology. The population universe was considered to be the patients attended in the Obstetrics and Gynecology service of the Martin Icaza Hospital between September 2024 and March 2025, applying a non-probabilistic sampling by convenience, with inclusion and exclusion criteria; for the application of the technique used was the survey to 83 patients of the hospital center. In this study it was determined that the level of knowledge about salpingectomy in patients of the Hospital General Martin Icaza de Babahoyo is at an acceptable level; therefore, patients who opted for salpingectomy had clearer information about the advantages of the procedure. However, women who decided not to have the procedure could present a general lack of understanding about salpingectomy.